Strengthening Collaboration to Facilitate the Mainstreaming of Training Materials in CSA And CIS into University Curricula in Burkina Faso - Kone, Daouda; Lamptey, Benjamin; Amponsah, William (2025)
The workshop at the WASCAL Competence Centre, Ouagadougou in Burkina Faso held on 30th October, 2024, was a follow-on to the achievements of WASCAL on the developed curricula and training programmes and to engage relevant stakeholders on the possible uptake and integration of the training materials into university curricula.